Sex and Gender Differences in Ventricular Arrhythmias - Rachel Koch Warnock; Roshan D Modi; Stacy B Westerman (US Cardiology Review)
Ventricular arrhythmias, including ventricular tachycardia and VF, commonly occur in patients with underlying cardiomyopathy. Sex differences exist in almost every aspect of ventricular arrhythmia from epidemiology, anatomy, and physiology to management and response to therapy. Some of these may be attributed to variations in etiology, types, and rates of cardiomyopathy as well as biological differences between males and females, but the full explanation for these differences remains incomplete. Additionally, women have been underrepresented in many trials studying therapies for ventricular arrhythmias including ICD placement and ablation; thus, there remains a need for continued research in this population. This review will discuss the differences between the sexes as well as outline opportunities for future research in women with ventricular arrhythmias.